Daily staffing trends and variation in Swiss long-term care from 2018–2023: A retrospective longitudinal analysis - Catherine Blatter; Michael Simon; Franziska Zúñiga (International Journal of Nursing Studies Advances)
Background: Workforce shortages present an ongoing challenge for long-term care service providers in Switzerland. After the COVID-19 pandemic, there is an urgent need to understand current workforce trends to strengthen the Swiss long-term care setting. Objective: We aimed to describe pre-, peri‑, and post-pandemic trends and variation of long-term care staffing. Design: We conducted a retrospective longitudinal analysis using daily administrative routine data from 2018 to 2023. Setting(s): A multisite long-term care facility in Switzerland with 180 beds. Methods: We applied a time-series decomposition – a method to distinguish trends from seasonal effects and residual variation – to describe trends and variation for three outcomes: a) the supply-demand-match (i.e., how did the available direct staff cover the actual care demand), b) the number of full-time absences (i.e., how many staff members were scheduled to work but were absent), and c) the number of temporary staff from an internal pool or external agency. We used means, confidence intervals, and percentages to summarize the yearly averages. Results: We linked data from 533,003 staff shifts and 387,585 resident days across the 6 study years. Overall, we observed constant variation but a decreasing trend of supply-demand match from a daily average number of staff of +6.88 [95% confidence intervals CI 6.86 - 6.90] in 2018 to -0.23 [95% CI -0.24 – -0.22] in 2023, meaning that for each year of the study, there was roughly one fewer staff member available per day for the same resident case mix. Simultaneously, daily staff absences increased from an average of 11.08 [95% CI 11.06 - 11.09] to 14.23 [95% CI 14.19- 14.27]. Absences decreased at the beginning of the pandemic (2020) but continuously increased from 2021 onwards, especially those with a duration of ≥ 1 week. As an organizational response, the number of shifts worked by temporary staff has increased from 5.5% in 2018 to 17.7% in 2023. Conclusions: We found a constant variation but a clinically noticeable downward trend of supply-demand-match from pre- to post-pandemic, largely driven by staff absences. It could not be reversed despite an increased deployment of temporary staff from both an internal pool and external agencies. We have revealed profound effects of the pandemic on an organization’s ability to meet the required care demand. Healthcare policy should consider alternative reimbursement strategies to alleviate the financial burden associated with a high number of absences. Registration: not registered